Analysis of Success Factor of The E-Learning System Using Delone and Mclean Models - Hidayat Ramadhani Winarno; Nilo Legowo (International Journal of Pedagogy and Teacher Education, 2024)
The effectiveness of e-learning systems has become a focal point in modern education, particularly with the global shift towards digital learning environments. This study employs the DeLone and McLean  Model, integrating the Technology Self-Efficacy (TSE) variable, to analyze the critical factors influencing e-learning success. Key dimensions, including information quality, system quality, service quality, system use, and user satisfaction, were evaluated through a comprehensive methodology involving Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data collected from 283 high school students in a suburban area reveal significant relationships, highlighting the pivotal roles of technology self-efficacy and system use in driving user satisfaction and overall e-learning success. The findings underscore that system use directly influences educational outcomes, with students’ confidence in navigating e-learning platforms emerging as a critical determinant of user satisfaction. Despite these successes, service quality and information accuracy areas present opportunities for refinement to further enhance user engagement and satisfaction. The study also emphasizes the adaptability and scalability of the proposed model for broader applications in diverse educational settings. This research contributes valuable insights into optimizing e-learning systems by addressing user-centric and technical aspects, ultimately supporting more effective digital learning platforms. The integration of TSE with the DeLone and McLean Model provides a robust framework for understanding and improving e-learning systems, offering actionable strategies for educational institutions aiming to align with the evolving demands of 21st-century learning.